Species diversity and composition, and above-ground carbon of mangrove vegetation in Jor Bay, East Lombok, Indonesia - Zulhalifah ZULHALIFAH; Abdul Syukur; Didik Santoso; Karnan KARNAN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Zulhalifah, Syukur A, Santoso D, Karnan. 2021. Species diversity and composition, and above-ground carbon of mangrove vegetation in Jor Bay, East Lombok, Indonesia. Biodiversitas 22: 2066-2071. Mangroves play a very important role to mitigate global warming. This study aimed to assess the species diversity and composition as well as the above-ground biomass and carbon content of mangroves in Jor Bay (Teluk Jor), Lombok Island, Indonesia. A purposive sampling method was implemented using transects and square plots as data collection techniques. The data was analyzed to reveal the frequency, density, dominance, above-ground biomass, and carbon content. The results of this study found seven mangrove species, namely Avicennia marina, Ceriops tagal, Rhizophora apiculata, Rhizophora stylosa, Sonneratia alba, Sonneratia caseolaris, and Lumnitzera racemosa. In general, Sonneratia alba was the most important species in terms of frequency, density, and dominance followed by Rhizophora apiculata. In total, mangrove vegetation in Jor Bay stored 697.45 ton C/ha, or equivalent to carbon monoxide uptake of 2559.63 CO2/ ha. In accordance with species composition, Sonneratia alba had the largest contribution to total carbon content with 453.76 tons C/ha), followed by Rhizophora apiculata with 74.47 tons C/ha. These findings suggest that mangrove vegetation in Jor Bay stored large amount of carbon in the form of above-ground biomass, implying the importance to preserve this area for carbon conservation.